(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
The behavior of 3‑(2‑bromoacetyl)isocoumarin (3‑(2‑bromoacetyl)-1H‑isochromen-1‑one) in reactions with N,N‑binucleophiles such as substituted 2‑aminopyridines (2‑amino-5‑methyl-, 2‑amino-5‑fluoro-, 2‑amino-5‑chloro- and 2‑amino-5‑bromopyridine), o‑phenylenediamines (4,5‑dimethyl- and 4,5‑difluoro-o‑phenylenediamine) and with 2‑aminothiazole was investigated. New isocoumarins with imidazo[1,2‑a]pyridins, quinoxalines and imidazo[2,3‑b]thiazole substituents in third position were synthesized. This transformation makes possible to obtain the target isocoumarins with preparative yields, which are weakly dependent by the substituents’ in the benzene ring of aminopyridine and phenylenediamine nature. Therefore, the using of this methodology opens wide possibilities for the synthesis of similar heterocyclic structures. The limiting factor for development of chemistry of isocoumarins’ with heterocyclic substituents in the third position that listed above is the availability of the initial 3‑acetylisocoumarin. So two previously known methods of 3‑acetylisocoumarin’s synthesis have been tested and improved. It was shows that cyclization oxopropyl ester of 2‑formylbenzoic acid to 3‑acetylisocoumarin by distillation in a vacuum occurs only at temperatures not lower than 165ºC (the pressure is 3.75 mm Hg). This method of cyclization provides pure 3‑acetylisocoumarin with a yield more than 40%. The earlier proposed by us "one-pot" method of 3‑acetylisocoumarin’s synthesis was improved. It was observed that formation of oxopropyl ester of 2‑formylbenzoic acid and its simultaneous cyclization in 3‑acetylisocoumarin, when the 2‑formylbenzoic acid and chloroacetone with the addition of triethylamine reacts in boiling dioxane, occurs more completely when the time of reacton increases from 1.5 to 4 h, and the yield of product accordingly increases from 60 to 70%.